Biochemical Aspects of Fumaric Acid Accumulation by Rhizopus arrhizus - Kenealy, William (1986)
The accumulation and excretion of fumaric acid, and to a lesser extent malic and succinic acids, by Rhizopus arrhizus occurs under aerobic conditions in a high-glucose medium containing a limiting amount of nitrogen and a neutralizing agent (CaCO(3)). An overall four-carbon dicarboxylic acid molar yield of up to 145% (moles of acid produced per mole of glucose utilized) is obtained after incubation for 4 to 5 days. Evidence is presented that fumarate is synthesized from pyruvate via a carboxylation reaction yielding oxaloacetate, which is then converted to malate and further on to fumarate via the reductive reactions of the tricarboxylic acid cycle. The possible formation of fumarate from the normal (oxidative) operation of the tricarboxylic acid cycle was not excluded by the data. Yield, (13)C nuclear magnetic resonance, and enzymatic activity studies were carried out in a strain of R. arrhizus which produces high levels of fumarate from glucose and carbonate. The observed high fumarate molar yield (greater than 100%) can therefore be explained in terms of the carboxylation of pyruvate and the operation of the reductive reactions of the tricarboxylic acid cycle under aerobic conditions.